Efficient Synthesis of 3,4-Disubstituted 7-Azaindoles Employing SEM as a Dual Protecting–Activating Group - Gyárfás, Piroska; Gerencsér, János; Wade, Warren S.; Ürögdi, László; Novák, Zoltán; Meyer, S. Todd (Synlett, 2019)
An efficient method for nucleophilic aromatic substitution on 7-azaindoles has been developed. The reaction is facilitated by the unique dual influence of SEM as both protecting and activating group, permitting mild conditions and short reaction times that are compatible with sensitive functional groups. The method is suitable for the synthesis of a broad range of products, most notably ethers.
Keywords: heterocycles; aromatic substitution; 7-azaindole; ethers